Development Of Junior High School Mathematics E-Book And Student Project Sheet Based On Integrated Merdeka Belajar Project Based Learning - Prihatin Ningsih Sagala; Eri Widyastuti (International Journal of Educational Research & Social Sciences, 2021)
The pandemic Covid-19 has resulted in limited direct interaction between teachers and students in the classroom. Learning goes from offline to online. The development of interactive e-book for Middle School Mathematics and student project sheets based on project based learning integrated Merdeka Belajar is very relevant to helping distance learning students to be actively involved in learning. Some of the features contained in the Junior High School Mathematics E-book include concept maps, instructions for using e-modules, embedding youtube links, google form links, audio features, teacher presentation videos, student assignment links, student project sheets and student evaluation links. These features make the e-book interesting and interactive. The independence of learning can be felt by students when choosing a project that is in accordance with the conditions of the surrounding environment. The results showed that the developed E-book in terms of the validity aspect of the material and media validator assessment was 3.67 with a very feasible category. The practical aspect seen from the responses of students and mathematics teachers was 3.50 (87.5%) and 3.64 (91%) in the very practical category, respectively. For the student project sheet developed to stimulate 6 aspects of student learning independence based on the learning independence instrument (Hidayati & Listyani, 2010) as many as 19 items. The given project sheet is able to stimulate students to achieve learning independence in the medium category (mean 3.27 on a scale of 5).